Finance and Development, September 1980. - International Monetary Fund. External Relations Dept. (Washington, D.C. : International Monetary Fund, 1980)
This paper highlights that despite severe limitations of resources, developing countries have made substantial progress during the past three decades in sending more children to school and in generally improving their education systems. Enrollment of children in schools at all levels has expanded at unprecedented rates. There has been a significant decline in the proportion of adults who are illiterate-from 44 percent in 1950 to 32 percent in 1975. Public expenditures for education have increased steadily in developing countries to reach roughly the same share of national product as in industrialized countries.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet